PENGARUH KEADILAN ORGANISASI, PEMBERDAYAAN KARYAWAN DAN KUALITAS KEHIDUPAN KERJA TERHADAP KOMITMEN ORGANISASI PADAPT. BPR NBP 33 KANTOR PUSAT BATANG KUIS - Christiani Sitorus; Rasmulia Sembiring; Junika Napitupulu (Universitas Methodist Indonesia, 2023)
This study aims to determine and analyze the effect of organizational justice, employee empowerment and quality of work life simultaneously on organizational commitment at PT. BPR NBP 33 Batang Kuis. This research was conducted at PT. BPR NBP 33 Batang Quis Head Office located on Jl. Medan - Batang Kuis No. 30 C, Bakaran Batu, Kec. Batang Kuis, Deli Serdang Regency, North Sumatra. The type of research in this study is quantitative data. The sampling method used in this study is the saturated sample method. The saturated sample method became the sample, so the number of samples in this study was 51 samples. Analysis of data using multiple linear regression analysis. The results showed that organizational justice had a positive and significant effect on organizational commitment at PT. BPR NBP 33 Batang Kuis with a t-count value of 2,245 > t-table 1,678 with a significance level of 0.030 <0.05. Employee empowerment has a positive and significant effect on organizational commitment at PT. BPR NBP 33 Batang Kuis with a t-count value of 2,256 > 1,678 with a significance of 0.029 < 0.05. Quality of work life has a positive and significant effect on organizational commitment at PT. BPR NBP 33 Batang Kuis with a t-count value of 2,411 > 1,678 with a significance of 0.020 < 0.05. Organizational justice, employee empowerment and quality of work life simultaneously have a positive and significant effect on organizational commitment at PT. BPR NBP 33 Batang Kuis.